2017
DOI: 10.5489/cuaj.4804
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating factors that dictate struvite stone composition: A multi-institutional clinical experience from the EDGE Research Consortium

Abstract: Introduction: Struvite stones account for 15% of urinary calculi and are typically associated with urease-producing urinary tract infections and carry significant morbidity. This study aims to characterize struvite stones based on purity of stone composition, bacterial speciation, risk factors, and clinical features. Methods: Retrospective data was collected from patients diagnosed with infection stones between 2008 and 2012. Stone analysis, perioperative urine cultures, bacterial speciation, and clinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…These findings suggest that future work should evaluate the effect of therapies for metabolic diseases on the incidence of struvite stone formation 45 . A retrospective study with 121 recovered struvite stones showed that only ~13% were homogenously composed of struvite, whereas ~87% contained struvite admixed with other mineral components, the order of abundance of which was calcium phosphate, calcium oxalate, calcium carbonate, and uric acid 47 . On average, ~35% of recovered struvite stones are composed of struvite with or without carbapatite, and ~65% comprise struvite stones admixed with calcium oxalate 45,46,48 .…”
Section: Key Pointsmentioning
confidence: 99%
“…These findings suggest that future work should evaluate the effect of therapies for metabolic diseases on the incidence of struvite stone formation 45 . A retrospective study with 121 recovered struvite stones showed that only ~13% were homogenously composed of struvite, whereas ~87% contained struvite admixed with other mineral components, the order of abundance of which was calcium phosphate, calcium oxalate, calcium carbonate, and uric acid 47 . On average, ~35% of recovered struvite stones are composed of struvite with or without carbapatite, and ~65% comprise struvite stones admixed with calcium oxalate 45,46,48 .…”
Section: Key Pointsmentioning
confidence: 99%
“…Urease negative bacteria such as Enterococcus spp., E. coli , Streptococcus spp., Citrobacter spp., Peptostreptococcus spp. and Bacteroides fragilis are commonly identified in the urine of struvite stone patients [ 5 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stone can grow rapidly occupying the renal calyces and pelvis damaging significantly the epithelium of the internal renal walls [ 4 ]. Data on the bacteriology of struvite stone cultures and urine cultures agree largely on the presence of infection agents [ 5 , 6 ]. Patients with kidney stone disease are more likely to have urinary tract infection (UTI) due to the invasion of uropathogens and their colonization in bladder or ascending infection to kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, these patients are prone tobe affected byurinary stones, due to several predisposing factorssuch ashypercalciuria, bone demineralization,dehydration 5 andtopiramate treatment forconcomitant epilepsy 6 .Struvite stones are a subset ofkidney stones, composed of magnesiumammonium phosphate (struvite)and calcium carbonate-apatite, whichform as a result of urinarytract infections with urease-producingpathogens. It is known thatthis type of stone is formed quickly,within a few weeks, in thepresence of urease producingbacteria 7 , from generasuch as Proteus,Providencia, Klebsiella, Staphylococcus. When theproduction ofammonia increases and the urine pH is high, thesolubility ofphosphate decreases, and struvite stones candevelop.…”
Section: Discussionmentioning
confidence: 99%